Detection of Pulmonary Embolism Based on Reduced Changes in Radiographic Lung Density During Cardiac Beating Using Dynamic Flat-panel Detector: An Animal-based Study - Tanaka, Rie; Tani, Tohru; Nitta, Norihisa; Tabata, Takahisa; Matsutani, Noritsugu; Muraoka, Shintaro; Yoneyama, Tsutomu; Sanada, Shigeru (Academic radiology, 2019)
To assess the capacity of dynamic flat-panel detector imaging without the use of contrast media to detect pulmonary embolism (PE) based on temporal changes in radiographic lung density during cardiac beating. Sequential chest radiographs of six pigs were acquired using a dynamic flat-panel detector system. A porcine model of PE was developed, and temporal changes in pixel values in the imaged lungs were analyzed during a whole cardiac cycle. Mean differences in temporal changes in pixel values between affected and unaffected lobes were assessed using the paired t test. To facilitate visual evaluation, temporal changes in pixel values were depicted using a colorimetric scale and were compared to the findings of contrast-enhanced images. Affected lobes exhibited a mean reduction of 49.6% in temporal changes in pixel values compared to unaffected lobes within the same animals, and a mean reduction of 41.3% compared to that before vessel blockage in the same lobe. All unaffected lobes exhibited significantly-increased changes in pixel values after vessel blockage (p < 0.01). In all PE models, there were color-deficient areas with shapes and locations that matched well with the perfusion defects confirmed in the corresponding contrast-enhanced images. Dynamic chest radiography enables the detection of perfusion defects in the lobe unit based on temporal changes in image density, even without the use of contrast media. Quantification and visualization techniques provide a better understanding of the circulation-induced changes depicted in dynamic chest radiographs.